Pengaruh Motivasi Intrinsik, Motivasi Ekstrinsik dan Lingkungan Kerja Terhadap Kinerja Pegawai - Ismail, Hamid; Noch, Muhamad Yamin; Mustajab, Duta (Paradoks : Jurnal Ilmu Ekonomi, 2024)
This study is associative research aimed at analyzing, identifying, and explaining the influence of Intrinsic Motivation, Extrinsic Motivation, and Work Environment on the Performance of Employees of the Financial and Asset Management Agency of Papua Province. The data in this research comprised 60 respondents out of a total population of 148 civil servants, representing 40.54%, determined through the Slovin sampling method with Simple Random Sampling as the probability sampling technique. The primary data source for this study was obtained by distributing questionnaires to all respondents. The statistical method employed to test hypotheses was multiple linear regression analysis using SPSS. Based on both partial and simultaneous testing results, it was found that intrinsic motivation, extrinsic motivation, and work environment significantly influence employee performance in the Financial and Asset Management Agency of Papua Province. This study highlights the dynamics within the Financial and Asset Management Agency of Papua Province and provides a deeper understanding of the factors influencing employee performance.